Volatile Profile Characterization of Winter Jujube from Different Regions via HS-SPME-GC/MS and GC-IMS - Yening Qiao; Jinfeng Bi; Qinqin Chen; Xinye Wu; Min Gou; Haonan Hou; Xinwen Jin; Giorgia Purcaro (Journal of Food Quality)
A combined untargeted and targeted approach was established for fingerprinting volatile organic compounds in winter jujubes from eight regions of China. Volatiles, including alcohols, aldehydes, acids, esters, and alkenes, were identified by gas chromatography-ion mobility spectrometry (GC-IMS). Benzyl alcohol, octanoic acid, 2-hexenal, linalool, 2-nonenal, and ethyl decanoate were the most common compounds present in all jujubes. Principal component analysis (PCA) from GC-IMS and untargeted E-nose showed that the main volatile organic compounds (VOCs) of most jujubes were similar. The volatile organic compounds of winter jujubes from Yuncheng city, Shanxi province, and Aksu region, Xinjiang province, were significantly different from those from other regions. 1-Penten-3-ol, ethyl hexanoate, methyl laurate, and 2-formyltoluene were the markers of XJAKS with green and fruity aroma, and SXYC could be labeled by acetone and 2-methoxyphenol with woody and pungent aroma. GC-IMS was an effective method for volatile fingerprinting of jujubes with high sensitivity and accuracy.